2015
DOI: 10.1080/87565641.2015.1028627
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Toddler Sleep Characteristics, Sleep Problems, and Temperament

Abstract: Two sources of information (parent reported sleep diaries and actigraph records) were used to investigate how toddler sleep characteristics (bed time/sleep onset, wake time/sleep offset, total nighttime sleep and total sleep time) are related to sleep problems and temperament. There were 64 toddler participants in the study. Consistent with studies of older children, parent reports differed from actigraph based records. The findings that parent reported and actigraph recorded sleep characteristics varied as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 28 publications
3
13
1
Order By: Relevance
“…We found a partial agreement between our data and those reported by Molfese et al (2015) on TD toddlers. These authors reported that toddlers with higher ratings for activity level (component of NS) had less actigraph-recorded nighttime sleep (in agreement with our findings that NS was correlated with a decreased sleep duration), and toddlers with higher soothability ratings (component of RD) had more actigraph-recorded total sleep (in agreement with our findings that higher RD was correlated with less mean wake episodes).…”
Section: Discussionsupporting
confidence: 91%
“…We found a partial agreement between our data and those reported by Molfese et al (2015) on TD toddlers. These authors reported that toddlers with higher ratings for activity level (component of NS) had less actigraph-recorded nighttime sleep (in agreement with our findings that NS was correlated with a decreased sleep duration), and toddlers with higher soothability ratings (component of RD) had more actigraph-recorded total sleep (in agreement with our findings that higher RD was correlated with less mean wake episodes).…”
Section: Discussionsupporting
confidence: 91%
“…First, sleep measures were only reported using parental reports, and we did not use objective measures, such as actigraphy. While parental reports and objective reports may disagree in some cases (Molfese et al, 2015), sleep reports are still considered valid for assessing sleep in young children. Moreover, use of parental reports enables the collection of larger samples.…”
Section: Discussionmentioning
confidence: 99%
“…Temperament, which can be conceptualized in terms of individual differences in tendencies to feel and express primary emotions (Goldsmith & Campos, 1990), is one of the factors most often proposed as likely to influence children's sleep (Molfese et al, 2015;Wolfson & Montgomery-Downs, 2013). De Marcas, Soffer-Dudek, Dollberg, Bar-Haim, and Sadeh (2015) suggested that child temperament may influence sleep in that reactivity to stimuli is a central aspect of temperament (Rothbart & Derryberry, 1981).…”
Section: Disentangling the Direction Of Associations Between Sleep Anmentioning
confidence: 99%